Synthesis, Anticancer Evaluation and DNA‐Binding Spectroscopic Insights of Quinoline‐Based 1, 3, 4‐Oxadiazole‐1, 2, 3‐triazole Conjugates. Issue 41 (7th November 2019) - Shamsi, Farheen; Aneja, Babita; Hasan, Phool; Zeya, Bushra; Zafaryab, M; Mehdi, Syed Hassan; Rizvi, M. Moshahid Alam; Patel, Rajan; Rana, Sandeep; Abid, Mohammad
Abstract: The present work involves a pharmacophore hybridization strategy to combine key biologically active scaffolds. The study led to the synthesis of quinoline based oxadiazole‐triazole conjugates with favorable physicochemical properties as anti‐cancer agents. Among the synthesized compounds 8(a–p), in vitro screening against a panel of four cancer cell lines identified compound 8k, with o ‐chloro substitution on the phenyl ring, as potent against human lung carcinoma (A‐549) cells (IC50 =5.6 μM), while showing no significant cytotoxicity upto 200 μM concentration in normal cells. Compound 8 k with o ‐chloro substitution induced nuclear morphological changes in A‐549 cells as visualized by DAPI (4, 6‐diamidino‐2‐phenylindole) and was shown to bind firmly with A−T rich region in DNA. Changes in DNA topology studied through gel electrophoresis and groove mode of binding to ct‐DNA through multi‐spectroscopic techniques were observed, further validated by molecular docking studies. Overall, the study illustrates successful hybridization strategy leading to compound 8 k as promising anticancer agent for further structural optimization and biological evaluation. Abstract : In silico ADME (Absorption, Distribution, Metabolism and Excretion) assessment demonstrated drug like properties of the synthesized quinoline based 1, 3, 4‐oxadiazole‐1, 2, 3‐triazole compounds. Out of 16 compounds, 8k with o ‐chloro substitution on phenyl ring, found to be active against A‐549 cells with an IC50 value of 5.6 μM. Nuclear morphological changes were observed by DAPI staining and photoactivated cleavage of pcDNA3.1 revealed changes in DNA topology induced by 8 k which was further validated through DNA binding studies by multi‐spectroscopic and molecular docking that showed binding of 8 k to minor groove of DNA.